2001
DOI: 10.1111/j.1572-0241.2001.03551.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound-Guided Celiac Plexus Block for Managing Abdominal Pain Associated With Chronic Pancreatitis: A Prospective Single Center Experience

Abstract: EUS-guided celiac plexus block appears to be safe, effective, and economical for controlling pain in some patients with chronic pancreatitis. Younger patients (<45 yr) and those having prior pancreatic surgery for chronic pancreatitis do not appear to benefit from this technique. Prophylactic antibiotics should be considered if acid suppressing agents are being taken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(77 citation statements)
references
References 35 publications
0
74
0
3
Order By: Relevance
“…Nine studies for chronic pancreatitis (N = 376) met the inclusion criteria [43,44,47,[49][50][51][52][53][54]. In these selected studies for chronic pancreatitis, three studies were published as full text articles [43,51,52] and six were abstracts [44,47,49,50,53,54]. Figure 1 shows the search results.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies for chronic pancreatitis (N = 376) met the inclusion criteria [43,44,47,[49][50][51][52][53][54]. In these selected studies for chronic pancreatitis, three studies were published as full text articles [43,51,52] and six were abstracts [44,47,49,50,53,54]. Figure 1 shows the search results.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, paraplegia has not been described after endoscopic ultrasoundguided celiac plexus block. The same group of investigators more recently published their prospective experience with endoscopic ultrasound-guided celiac plexus blocks with steroids in 90 patients with pain resulting from chronic pancreatitis [43]. A significant improvement in pain scores occurred in 55% of these patients.…”
Section: Evaluation/treatmentmentioning
confidence: 96%
“…However, recent randomized comparisons of endoscopic versus surgical management of ductal obstruction have suggested the superiority of surgical interventions. In one study [44], patients with [37][38][39][40][41][42][43][44][45] alcohol despite the diagnosis of chronic pancreatitis has a 50% mortality rate at 5-year follow-up. If they abstain from drinking, it takes more than 25 years to have a similar mortality rate.…”
Section: Evaluation/treatmentmentioning
confidence: 99%
“…The procedure is less efficacious in chronic pancreatitis however; Gress, et al . demonstrated that neurolysis with corticosteroids (triamcinolone) reduced pain scores beyond 12 weeks in 26% of subjects 64 .…”
Section: Eus‐guided Injection Therapymentioning
confidence: 99%